Arabidopsis molybdenum cofactor sulfurase ABA3 contributes to anthocyanin accumulation and oxidative stress tolerance in ABA-dependent and independent ways. Issue 1 (December 2018) - Watanabe, Shunsuke; Sato, Muneo; Sawada, Yuji; Tanaka, Maho; Matsui, Akihiro; Kanno, Yuri; Hirai, Masami; Seki, Motoaki; Sakamoto, Atsushi; Seo, Mitsunori
Abstract Arabidopsis ABA3 is an enzyme involved in the synthesis of the sulfurated form of the molybdenum (Mo) cofactor (MoCo), which is required for the enzymatic activity of so-called Mo enzymes such as aldehyde oxidase (AO) and xanthine dehydrogenase (XDH). It has been reported that AO and XDH are essential for the biosynthesis of the bioactive compounds, ABA and allantoin, respectively. However, aba3 mutants often exhibit pleiotropic phenotypes that are not explained by defects in ABA and/or allantoin biosynthesis, leading us to hypothesize that ABA3 regulates additional metabolic pathways. To reveal the currently unidentified functions of ABA3 we compared transcriptome and metabolome of the Arabidopsisaba3 mutant with those of wild type and a typical ABA-deficient mutantaba2 . We found that endogenous levels of anthocyanins, members of the flavonoid group, were significantly lower in theaba3 mutant than in the wild type or theaba2 mutant under oxidative stress. In contrast, mutants defective in the AO and XDH holoenzymes accumulated significantly higher levels of anthocyanins when compared withaba3 mutant under the same conditions. Our findings shed light on a key role of ABA3 in the ABA- and allantoin-independent accumulation of anthocyanins during stress responses.